Le rôle fondateur du paysage dans la création des villes coloniales marocaines - Mounia Bennani (Projets de Paysage)
In April 2010, during the 40th anniversary of Earth Day, Rabat – the capital city of Morocco – was awarded the title of “Green City”. This status of green city harks back to the creation of the modern colonial city during in the 1920s – a “landscape-city” that finds its foundations in its natural and historical heritage. Rabat and Marrakesh were converted to model garden-cities at the time of the French Protectorate, but following two distinct principles. In Rabat, the open spaces system was conceived in 1913 by Jean-Claude Nicolas Forestier, from a “special plan of open spaces” ; while in Marrakesh, the parks and gardens network already existed. Thus, the main urban objective of the protectorate was to preserve the existing landscape heritage and to make it fit into the planning project of the new European districts. Nearly a century later, Rabat’s landscape heritage is at the heart of the matter : the public gardens created in the 1920s, and which are the lungs of today’s city, have been classified and put on the list of the cultural heritage list ; the story of the “park system” known such as in Rabat is taught in the architecture schools, and the urban development project of Rabat is planning to raise the current ratio from 20 m² of green space per inhabitant to 30 m².